Community Empowerment through Local Resource Management: A Case Study of the Social Forestry Scheme in Yehembang Kangin Village - Tahsa Ayu Seva; Muhammad Rizky Andika Putra; I Gede Sugiantara (Indonesian Journal of Social Responsibility Review (IJSRR), 2025)
Jembrana Regency has been facing serious challenges due to gradual forest degradation since 1998, triggered by the practice of ngawen, or the conversion of forest areas into short-term crop plantations. Jembrana Regency experienced the highest rate of tree cover loss in Bali between 2001 and 2020, according to data from Global Forest Watch. In response to this ecological crisis, the Jembrana Regency Government, together with the West Bali Forest Management Unit (UPTD KPH Bali Barat), initiated strict monitoring efforts and strategic partnerships with local communities, including Village Forest Management Institutions (LPHD) and Forest Farmer Groups (KTH). This study focuses on highlighting the significant transformation undertaken by KTH Banu Giri Lestari, which was initially involved in ngawen practices. Today, it has become a pioneer of environmental conservation through a partnership in the corporate social responsibility (CSR) program of PT Pertamina Patra Niaga AFT Ngurah Rai, titled 'Sri Wana Lestari'. This program integrates ecological, social, and spiritual approaches based on local wisdom known as ‘Wana Kertih’, which represents one of the core components of the ‘Tri Hita Karana’ philosophy. It also includes awareness-raising activities, capacity building, and the development of enterprises based on Non-Timber Forest Products (NTFPs). Through multi-stakeholder synergy, this empowerment model demonstrates significant potential in building a sustainable and inclusive forest management ecosystem. The findings affirm that cross-sector collaboration rooted in local cultural approaches can serve as an effective strategy to address deforestation and enhance the socio-ecological resilience of forest-dependent communities.